Pharmacokinetics and pharmacodynamics of voxelotor (GBT440) in healthy adults and patients with sickle cell disease. Issue 6 (31st March 2019) - Hutchaleelaha, Athiwat; Patel, Mira; Washington, Carla; Siu, Vincent; Allen, Elizabeth; Oksenberg, Donna; Gretler, Daniel D.; Mant, Timothy; Lehrer‐Graiwer, Josh
Abstract : Aims: Voxelotor (previously GBT440) is a haemoglobin (Hb) modulator that increases Hb‐oxygen affinity, thereby reducing Hb polymerization and sickling of red blood cells (RBCs), being developed as a once‐daily oral drug to treat sickle cell disease (SCD). This first‐in‐human study evaluated the safety, tolerability, pharmacokinetics and pharmacodynamics of voxelotor in healthy volunteers and SCD patients. Methods: A total of 40 healthy volunteers (100, 400, 1000, 2000 or 2800 mg) and 8 SCD patients (1000 mg) were randomly assigned to a single dose of voxelotor once daily ( n = 6 per group) or placebo ( n = 2 per group). Twenty‐four healthy volunteers received multiple doses of voxelotor once daily for 15 days (300, 600 or 900 mg, n = 6 per group) or placebo ( n = 2 per group). Results: Voxelotor was well tolerated and exhibited a linear pharmacokinetic profile and a half‐life ranging from 61 ± 7 h to 85 ± 7 h. High partitioning into the RBC compartment provides evidence of highly specific binding to Hb. Voxelotor exhibited a concentration‐dependent left‐shift of oxygen equilibrium curves. Percent Hb modification following 900 mg voxelotor for 15 days was 38 ± 9%. Terminal half‐life of voxelotor in SCD patients (50 ± 3 h) was shorter than in healthy volunteers. Evaluation of erythropoietin, exercise testing, and haematologic parameters were consistent with normal oxygen delivery during both rest and exercise. Conclusion: This first‐in‐human study demonstrates voxelotor was well tolerated in SCD patients and healthy volunteers and established proof of mechanism on increasing Hb‐oxygen affinity.